KEAMANAN TRANSAKSI DAN PENGARUHNYA TERHADAP KEPUASAN PENGGUNA PADA PLATFORM E-COMMERCE SHOPEE - Yolanda Ardestya Linanjung; Natoil Natoil; Agung Prastyawan; Siti Khayatun (Sekolah Tinggi Ilmu Ekonomi Semarang, 2026)
This study aims to determine the effect of user trust, transaction security, and information quality on user satisfaction on the Shopee marketplace The research method used was a quantitative survey approach. Data were collected through questionnaires distributed to 53 respondents, who were Shopee users. Data analysis techniques included descriptive statistical tests, classical assumption tests (normality, multicollinearity, and heteroscedasticity tests), multiple linear regression analysis, t-tests, F-tests, and the coefficient of determination (R²) test. The results showed that partially, User Trust had a calculated t-value of 2.225 with a significance value of 0.031. This significance value is less than 0.05 (0.031 < 0.05), thus concluding that User Trust has a positive and significant effect. Transaction Security has a calculated t-value of 3.518 with a significance value of 0.001. This value is less than 0.05 (0.001 < 0.05), so it can be concluded that transaction security has a positive and significant effect on user satisfaction, and Information Quality has a t-value of 2.094 with a significance value of 0.041. This significance value is less than 0.05 (0.041 < 0.05), so it can be concluded that information quality has a positive and significant effect on user satisfaction. The results of the regression analysis show that transaction security is the most dominant variable in influencing user satisfaction. In addition, the Adjusted R Square value of 0.554 indicates that 55.4% of user satisfaction can be explained by the variables of user trust, transaction security, and information quality, while the remaining 44.6% is influenced by other variables outside the study. Thus, it can be concluded that increasing user trust, transaction security, and information quality can increase user satisfaction on the Shopee marketplace